Analysis of emerging trends and hot spots in respiratory biomechanics from 2003 to 2022 based on CiteSpace - Huang, Xiaofei; Zheng, Jiaqi; Ma, Ye; Hou, Meijin; Wang, Xiangbin (Frontiers in Physiology, 2023)
With the global prevalence of coronavirus disease 2019 , an increasing number of people are experiencing respiratory discomfort. Respiratory biomechanics can monitor breathing patterns and respiratory movements and it is easier to prevent, diagnose, treat or rehabilitate. However, there is still a lack of global knowledge structure in the field of respiratory biomechanics. The purpose of this study is to demonstrate the emerging trends and hot spots in the field of respiratory biomechanics through bibliometric software.The number of annual publications gradually increased over the past 20 years. Medical Physics published the most articles and had the most citations in this study. The United States was the most influential country, with the highest number and centrality of publications. The most productive and influential institution was Harvard University in the USA. Keall PJ was the most productive author and MCCLELLAND JR was the most cited authors The article by Keall PJ ( 2006) article (cocitation counts: 55) and the article by McClelland JR (2013) were the most representative and symbolic references, with the highest cocitation number and centrality, respectively. The top keywords were "radiotherapy", "volume", and "ventilation". The top frontier keywords were "organ motion", "deep inspiration", and "deep learning". The keywords were clustered to form seven labels.With the help of CiteSpace software, we aim to help researchers identify potential collaborators and collaborating institutions, hotspots and research frontiers in respiratory biomechanics. Currently, the main area of research in respiratory biomechanics is respiratory motion related to imaging techniques. Future research may focus on respiratory assistance techniques and respiratory detection techniques. At the same time, respiratory monitoring devices will be further developed in the future to enable people to monitor their health status anytime, anywhere. At the same time, in the future, we will pay attention to personalized medicine and precision medicine, so that people can monitor their health status anytime and anywhere.